2021
DOI: 10.1136/bmjgh-2021-006446
|View full text |Cite
|
Sign up to set email alerts
|

Excess deaths reveal unequal impact of COVID-19 in Ecuador

Abstract: Latin America has struggled to control the transmission of COVID-19. Comparison of excess death (ED) rates during the pandemic reveals that Ecuador is among the highest impacted countries. In this analysis, we update our previous findings with the most complete all-cause mortality records available for 2020, disaggregated by sex, age, ethnicity and geography. Our study shows that in 2020, Ecuador had a 64% ED rate (95% CI 63% to 65%) or 64% more deaths than expected. Men had a higher ED rate, 75% (95% CI 73% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 6 publications
1
29
1
4
Order By: Relevance
“… 22 A large excess death rate of 64% more deaths in 2020 than 2019 were also reported in Ecuador, where it was found that indigenous populations had four times the excess death rate of the majority mestizo group, indicating unequal impact of COVID on vulnerable populations. 23 …”
Section: Discussionmentioning
confidence: 99%
“… 22 A large excess death rate of 64% more deaths in 2020 than 2019 were also reported in Ecuador, where it was found that indigenous populations had four times the excess death rate of the majority mestizo group, indicating unequal impact of COVID on vulnerable populations. 23 …”
Section: Discussionmentioning
confidence: 99%
“…When working with national data in the first half of 2020 8 , Orellana et al (2021) showed excess deaths of 112% in Manaus (state of Amazonas, Brazil) and 72% in Fortaleza (state of Ceará, Brazil), above the MRJ, which had 42%. In Ecuador, the percentage of excess deaths was 64% in 2020, and only 20% of these were attributed to COVID-19, mainly due to the low number of available tests 19 . In another study, researchers estimated an excess of 73% in Peru, the highest in the group of 77 countries studied 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Variations between countries may be attributed, at least in part, to differences in the extent of COVID-19 testing, political leadership, wealth, and equality, as well as the existence of informal economies and having regions and populations with limited access to health services [ 19 , 20 ]. In Ecuador, for example, all-cause mortality rose by 64% in 2020, and was markedly higher in indigenous groups, which have been historically underserved by healthcare services [ 21 ]. Notably, confirmed COVID-19 deaths in Ecuador accounted for only 21% of excess deaths, highlighting limitations in diagnostic testing [ 21 ].…”
Section: Regional Epidemiology Of Covid-19mentioning
confidence: 99%
“…In Ecuador, for example, all-cause mortality rose by 64% in 2020, and was markedly higher in indigenous groups, which have been historically underserved by healthcare services [ 21 ]. Notably, confirmed COVID-19 deaths in Ecuador accounted for only 21% of excess deaths, highlighting limitations in diagnostic testing [ 21 ].
Fig.
…”
Section: Regional Epidemiology Of Covid-19mentioning
confidence: 99%